INNOVATIVE USE OF BANANA PEEL FLOUR IN BROWNIES PRODUCTION: NUTRITIONAL AND SENSORY IMPACTS - Natalia Angel Auwdinata; Nazwa Nakiyah Nabila; Khadijah Raihana Putri Nufrianto; Michael Ricky Sondak (RADJA PUBLIKA, 2025)
This study examines the innovative application of banana peel flour as a partial substitute for wheat flour in brownie production, with a focus on its nutritional benefits and sensory impact. As banana peels are a commonly discarded agricultural by-product despite their rich composition of dietary fiber, antioxidants, and minerals, their transformation into flour presents a valuable approach to waste reduction and functional food development. The research involved formulating brownies with varying concentrations of banana peel flour at 10%, 25%, and 50%. Each formulation was evaluated based on proximate composition and sensory attributes, including color, aroma, taste, and texture. Results indicated that substitution levels of up to 25 percent improved nutritional value, particularly in terms of fiber and mineral content, without significantly compromising consumer acceptability. The 10 percent formulation achieved the highest scores across all sensory parameters, while the 50 percent formulation exhibited reduced palatability due to increased bitterness and changes in texture. These findings highlight the potential of banana peel flour as a sustainable and nutritious ingredient in baked products when used in optimal proportions.